DEVELOPING ENGLISH LEARNING MATERIAL FOR SPECIFIC PURPOSES WITH CULTURE PERSPECTIVE - Yusmei, Nining; Sesmiarni, Zulfani; Maimori, Romi; Albert, Albert (Lembaga Penelitian dan Pengabdian Masyarakat, Universitas Pahlawan Tuanku Tambusai, 2022)
Abstract Lecturer in education works closely with colleagues in Campus. Lectures are materials developers at College, in that they involved every day in matching materials to the needs of their learners. In order to do this, they select, adapt and supplement materials when preparing their lessons and they make decisions about their materials throughout their lessons in response to their learner’s reactions. This paper describes teaching/learning materials development for ELT with culture perspective in west Sumatera that Tiga Tungku Sajarangan (the three important leadherships). This paper discusses materials development in reading skill.